2021
DOI: 10.1093/brain/awab202
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of plasticity-based cognitive training in mild traumatic brain injury

Abstract: Clinical practice guidelines support cognitive rehabilitation for people with a history of mild traumatic brain injury (mTBI) and cognitive impairment, but no class I randomized clinical trials have evaluated the efficacy of self-administered computerized cognitive training. The goal of this study was to evaluate the efficacy of a self-administered computerized plasticity-based cognitive training programmes in primarily military/veteran participants with a history of mTBI and cognitive impairment. A multisite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Secondly, their neurocognitive status largely reflected the “natural” course of illness recovery, not affected by systematic neuropsychiatric interventions. These characteristics render the present sample suitable to assess the chronic impact of mTBI given the, at least modest, effect of suspected malingering (Ross, Putnam, and Adams, 2006 ), and the documented impact of cognitive (Mahncke et al, 2021 ) and physical rehabilitation (Snyder et al, 2021 ) upon cognitive recovery.…”
Section: Discussionmentioning
confidence: 96%
“…Secondly, their neurocognitive status largely reflected the “natural” course of illness recovery, not affected by systematic neuropsychiatric interventions. These characteristics render the present sample suitable to assess the chronic impact of mTBI given the, at least modest, effect of suspected malingering (Ross, Putnam, and Adams, 2006 ), and the documented impact of cognitive (Mahncke et al, 2021 ) and physical rehabilitation (Snyder et al, 2021 ) upon cognitive recovery.…”
Section: Discussionmentioning
confidence: 96%
“…TBI is one of the most common traumatic injuries which can cause long-lasting cerebral damage and cognitive deficits [25]. Elucidating the potential molecular mechanisms and therapeutic targets for improving cognitive function helps to improve the clinical prognosis and alleviate the burden on patients suffering from TBI [26]. Transcriptomic profiling is a powerful tool that can identify the genes differ-entially expressed in specific physiological and pathological states and discover new diagnostic or therapeutic targets [27].…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies, including six RCTs and one small prospective comparative study, [82][83][84][85][86][87][88] were identified on cognitive rehabilitation. One study involved adolescents with acute concussion.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%